(untitled) (Eastern Medical College Journal, 2025)
Background: Stroke, a leading cause of global mortality, includes ischemic and hemorrhagic types, with ischemic strokes being the most prevalent. There are some modifiable and nonmodifiable risk factors of stroke. This aim of the study was to evaluate the sociodemographic factors and assess the stroke risk factors in a tertiary care hospital. Materials and Methods: This prospective observational study was conducted at Eastern Medical College & Hospital from July 2023 to December 2023, involving 120 patients with stroke. Stroke was diagnosed by clinical evaluation, imaging studies (CT/MRI) and neurological examination. Institutional ethical clearance was obtained. Data was collected with informed consent from patients or their guardians, including demographic details and stroke risk factors and then analyzed using SPSS V23.0. Results: Among the 120 participants, the highest stroke incidence was in the 51-60 years (25.83%) and 41-50 years (21.67%) age groups, with a mean age of 24.19 years. Altered consciousness was observed in 24.17% of patients followed by limb weakness in 20%. Hypertension (35%), diabetes mellitus (17%) and dyslipidaemia (17%) were common pre-existing conditions. Tobacco use emerges as the most prevalent risk factor, affecting 45% of the patients, followed by an overweight 31%. Conclusion: This study highlights the significant role of sociodemographic factors and modifiable risk factors in the development of stroke. The high prevalence of hypertension, diabetes, smoking, and physical inactivity among stroke patients in this study underscores the need for targeted prevention strategies. Eastern Med Coll J. July 2025; 10 (1): 40-44